Osteoporosis and Physical training - Malliou, Παρασκευή; Gioftsidou, Ασηµένια; Delaporta, Αικατερίνη; Godolias, Γεώργιος (Inquiries in Physical Education and Sport, 2004)
Osteoporosis is a disease in which the bones thin and become more porous. The disease generally progresses without pain until a bone fractures. Risk factors for osteoporosis include a small body frame, excessive alcohol consumption, cigarette smoking, loss of estrogens, family history of osteoporosis, low dietary calcium intake, and use of some medications. Proper exercise programs, proper nutrition, avoiding smoking and minimizing alcohol consumption are some of the advice that a patient has to follow. According to present review two types of exercise are proposed to maintain healthy bones: weight-bearing and resistance exercises. Weight-bearing exercises involve the bones and muscles working against gravity. Jogging, walking, stair climbing and dancing are examples of weight-bearing exercises. Resistance exercises use muscular strength to increase muscle mass and strengthen bone. In addition balance exercises must be included in the exercise program in order to increase the balance ability of the patient and reduce the falls and the related problems.